Korelasi Subtes IST dengan Nilai Mata Pelajaran di Sekolah yang Berada di Bawah Naungan Yayasan ‘X’ Bandung - Lisa Imelia; Heliany Kiswantomo (Universitas Kristen Maranatha, 2018)
The purpose of this research is to measure the Correlation between IST Subtest with Academis Scores at Schools in Yayasan ‘X’ Bandung. IST is one of the intelligence test currently used to measure students' intelligence at school. Student achievement is influenced by intelligence. This study uses multiple correlational design, to measure correlation strength between the two variables. Respondent are are 10th grade high school students in Yayasan ‘X’ Bandung. The instrument used in this study is the IST to measure the intelligence. Academic scores taken from student scores in every lesson. The results of this study indicate that the function of intelligence correlates with almost all forced lessons, except for cultural arts, singing, design and sports. For subjects of IPA concentration, intelligence function is supposed to be a predictor of Physics, Mathematics, Biology and Chemistry, whereas for subjects of IPS concentration, intelligence function can only be predictor of geography.